(untitled) (South East Asia Journal of Public Health, 2019)
Severe dengue virus (DENV) manifestations commonly occurred in secondary infections. Serology assay using rapid immunochromatographic test is one of diagnostic modalities used in community setting. The aim of this research was to evaluate the use of a serial rapid immunochromatographic test in establishing DENV infection in community pa-tients. This cross-sectional study was conducted in Clinical Microbiology Laboratory Department of Microbiology Faculty of Medicine Universitas Indonesia Jakarta using paired stored sera from community-based DENV patient col-lected in 2010. Samples with positive nonstructural protein 1 (NS1) result were subjected to hemagglutination inhibi-tion (HI) assay. Serial NS1, IgM, IgG, clinical features, and virus serotype result from previous study were taken as secondary data and compared with HI assay result as gold standard. For rapid immunochromatographic test vs HI analysis, both results were classified as ‘Primary Infection’ and ‘Secondary Infection’. A total of 25 samples fulfilled the inclusion criteria. The proportion of primary and secondary infection according to Bioline SD Dengue Duo was 44% and 56%, respectively. In the other side, 23 samples (92%) were classified as secondary infection by mean of HI assay; the rest was primary infection. The highest agreement rate between serial rapid immunochromatographic test and HI was 68%. The rapid test can detect IgM and IgG as early as on 3rd day of fever. The results of rapid immunochromatographic test were in accordance with HI if it was examined within 3-7 day of fever and therefore can replace HI for determining DENV infection whether primary or secondary. South East Asia Journal of Public Health Vol.8(1) 2018: 17-21